Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Bai, Hui-lin; Feng, Wen-kai; Li, Shuang-quan; Ye, Long-zhen; Wu, Zhong-teng; Hu, Rui; Dai, Hong-chuan; Hu, Yun-peng; Yi, Xiao-yu; Deng, Peng-cheng (Journal of mountain science, 2022)
Affected by typhoons over years, Fujian Province in Southeast China has developed a large number of shallow landslides, causing a long-term concern for the local government. The study on shallow landslide is not only helpful to the local government in disaster prevention, but also the theoretical basis of regional early warning technology. To determine the whole-process characteristics and failure mechanisms of flow-slide failure of granite residual soil slopes, we conducted a detailed hazard investigation in Minqing County, Fujian Province, which was impacted by Typhoon Lupit-induced heavy rainfall in August 2021. Based on the investigation and preliminary analysis results, we conducted indoor artificial rainfall physical model tests and obtained the whole-process characteristics of flow-slide failure of granite residual soil landslides. Under the action of heavy rainfall, a granite residual soil slope experiences initial deformation at the slope toe and exhibits development characteristics of continuous traction deformation toward the middle and upper parts of the slope. The critical volumetric water content during slope failure is approximately 53%. Granite residual soil is in a state of high volumetric water content under heavy rainfall conditions, and the shear strength decreases, resulting in a decrease in stability and finally failure occurrence. The new free face generated after failure constitutes an adverse condition for continued traction deformation and failure. As the soil permeability (cm/h) is less than the rainfall intensity (mm/h), and it is difficult for rainwater to continuously infiltrate in short-term rainfall, the influence depth of heavy rainfall is limited. The load of loose deposits at the slope foot also limits the development of deep deformation and failure. With the continuous effect of heavy rainfall, the surface runoff increases gradually, and the influence mode changes from instability failure caused by rainfall infiltration to erosion and scouring of surface runoff on slope surface. Transportation of loose materials by surface runoff is an important reason for prominent siltation in disaster-prone areas.